Analisis Perpindahan Penggunaan Merek Handphone Dikalangan Mahasiswa Menggunakan Rantai MARKOV (Studi Kasus: Mahasiswa Universitas HKBP Nommensen Pematang Siantar Tahun 2019) - Ruth Preccilya Situmorang; Debora Exaudi Sirait; Juli Antasari Sinaga (CV Putra Publisher, 2024)
The aim of the research is to form a Markov Chain from switching cellphone brands among UHKBPNP students. This research method uses quantitative methods with a survey research type. The data collection technique used was by collecting questionnaires. The results of research and discussion of cellphone brand switching among students show that the cellphone brand that has the most loyal users is Oppo (40.59%). Meanwhile, the cellphone brand that uses the least loyalty is iPhone (0.4%). The Xiaomi cellphone brand was able to beat Vivo, Realme, Redmi, iPhone and there was quite intense competition between the Redmi and Vivo brands.